A middle-range theory for developing clinical reasoning skills in undergraduate midwifery students - Olivia B. Baloyi; Ntombifikile G. Mtshali (Elsevier, 2018)
Background: Clinical reasoning remains central in midwifery care in the light of uncontrollable high maternal mortality rates and errors in midwifery practice. However, there is no consensus, locally and internationally, on how clinical reasoning skills can be developed in undergraduate students particularly within midwifery context. Aim: This article present the middle-range-theory for developing clinical reasoning skills within undergraduate midwifery students. Methods and analysis: Qualitative and grounded theory approach, underpinned by Social Constructivism Paradigm, was used. Data were collected over twelve months, using multiple methods of observations, interviews and document analysis. The participants comprised of midwifery students, the 2016 and 2017 cohorts and midwifery educators. A total of 16 focus group discussions and 12 individual in-depth interviews were conducted. Data collection and initial data analysis occurred simultaneously using coding process, with constant comparative analysis at each phase. Ethical clearance was obtained from the University Ethics Committee, with the Protocol reference number HSS/1288/016D. Findings: Developing clinical reasoning skills emerged as the main concept in the middle-range theory that was generated in this study, supported by major concepts, which included context, nature of the curriculum, clinical reasoning process, pillars including individual and system related outcomes. Conclusion: The discussion in this study offers an opportunity to equip the midwifery educators with the necessary skills and knowledge necessary to produce midwifery graduates who are in line with the complexities of the healthcare system not only confined to the South African borders.